Knowledge, Attitudes, and Practices Regarding Intravenous Fluids Among Physicians in the West Bank of Palestine: A Cross‐Sectional Study - Mamoun Swaileh; Razan Rabi; Dina Abugaber; Yusuf B. Dawabsheh; Murad A. M. Karajeh; Halla Albada; Ziad Radad; Sa'ed H. Zyoud; Moutaz W. Sweileh (Health Science Reports, 2026)
ABSTRACT Background and Aims Inappropriate use of intravenous (IV) fluids is associated with increased morbidity. Despite their routine use in hospitalized patients, physicians' knowledge, attitudes, and practices (KAP) regarding IV fluids remain inadequately investigated. This study assessed physicians' KAP in the West Bank, Palestine. Methods A cross‐sectional online survey targeted physicians caring for hospitalized adult patients in West Bank hospitals. A questionnaire assessed demographic and professional characteristics, knowledge, attitudes, practices, and perceived barriers regarding IV fluids. Knowledge scores were converted into percentages and summarized using medians/interquartile ranges (IQR). Comparison of knowledge scores across physician subgroups was performed using the Mann–Whitney U test and the Kruskal–Wallis test, with Dunn's post hoc test and a Holm adjustment where appropriate. Attitudes, practices, and perceived barriers were presented as frequencies and percentages. Results Of 256 participants (median age = 28 years, IQR 25–33), there were 173 (67.6%) males and 72 (28.1%) reported receiving formal IV fluids training during the previous 2 years. Residents and fellows comprised 101 (39.5%). The median knowledge score was 57.7% (IQR 35.7). The highest correct response in the knowledge section ( n = 223, 87.1%) was observed for identifying hyperchloremic metabolic acidosis as a complication of 0.9% saline, while the lowest correct response ( n = 67, 26.2%) was observed for identifying IV fluids not recommended for routine use. Knowledge scores differed significantly by departmental affiliation ( P < 0.001) and professional position status ( P = 0.03). Regarding attitudes, 116 (45%) agreed/strongly agreed that balanced crystalloids should be preferred over 0.9% saline in most ICU patients. In practice, 140 (54.7%) reported using 0.9% saline as the first‐line fluid in their practice. The most cited barrier was the absence of institutional guidelines ( n = 157, 61.3%). Conclusion Physicians demonstrated average knowledge, suboptimal practices, and limited agreement with evidence‐based attitudes toward IV fluid therapy. Educational interventions and hospital protocols are needed to help improve KAP.